Alteration of the Basal Membrane Integrity in Orthodontic Treatment-Induced Gingival Enlargement - Victor Hugo Simancas Escorcia; Alejandra Herrera-Herrera; Antonio Díaz Caballero (Editorial Ciencias Médicas, 2023)
Introduction: Orthodontic treatment-induced gingival enlargement is a progressive, localized or generalized increase in gingival tissue. Objective: To determine morphologic aspects in the basal membrane of the gingival tissue in patients with orthodontic treatment-induced gingival enlargement. Methods: A descriptive and cross-sectional study was carried out, in which gingival tissues of patients with orthodontic treatment-induced gingival enlargement (test group: n=5) and healthy individuals (control group: n=5) were analyzed by histological and immunohistochemical analysis with the polyclonal antibody anticytokeratin 14. Grade 1 and grade 2 disrupted basal membrane were identified. The statistical program R (version 4.0.2) for Windows was used. Significance was declared if p was greater than 0.05. Results: The presence of disrupted basal membranes was observed in all the patients from the test group. These individuals presented a greater number of morphological changes in the gingival tissue. Compared to the control group (p < 0.001), statistically significant values were observed for cases of disrupted basal membrane (grade I) and disruptions surrounded by epithelial cells or gingival fibroblasts (grade II). Conclusion: The epithelial tissue of patients with orthodontic treatment-induced gingival enlargement shows an evident loss of the basal membrane integrity. These discontinuities are suggestive of a considerable increase in epithelial plasticity in patients with orthodontic treatment-induced gingival enlargement.